2004
DOI: 10.1161/01.hyp.0000137380.91476.fb
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Endothelial Release of Tissue-Type Plasminogen Activator in Patients With Chronic Kidney Disease and Hypertension

Abstract: Abstract-We have shown that the capacity for local release of tissue-type plasminogen activator (tPA) from the vascular endothelium is impaired in patients with primary hypertension. Because this response is an important protective mechanism against intravascular clotting, we investigated whether this system is also defective in patients with advanced chronic kidney disease and hypertension. Nine nondiabetic nonsmoking men with chronic kidney disease (glomerular filtration rate 11 to 28 mL/minϫ1.73 m 2 ; aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 35 publications
(25 reference statements)
3
30
0
Order By: Relevance
“…Measuring the capacity for tPA release may provide additional and novel insights into endothelial-like cell function. For example, it has been suggested that tPA release may be a more sensitive marker of endothelial dysfunction than previously thought, since it has been reported that patients with hypertension show normal endothelial-dependent vasodilation yet impaired tPA release [45]. HE-like cells cultured on POC secrete tPA in nonstimulated cultures and respond to thrombin stimulation by upregulating tPA secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the capacity for tPA release may provide additional and novel insights into endothelial-like cell function. For example, it has been suggested that tPA release may be a more sensitive marker of endothelial dysfunction than previously thought, since it has been reported that patients with hypertension show normal endothelial-dependent vasodilation yet impaired tPA release [45]. HE-like cells cultured on POC secrete tPA in nonstimulated cultures and respond to thrombin stimulation by upregulating tPA secretion.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced capacity to release t-PA has also been observed in subjects with an increased risk of myocardial infarction, i.e. smokers [7,8] and hypertensives [9,10]. It has, however, recently been shown, that the impairment in the latter group is reversible as it can be restored by anti-hypertensive therapy [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients with reduced renal function are more likely to develop pulmonary thromboembolism than those with normal kidney function [7]. Possible mechanisms for the phenomenon include enhanced activation of factor XIIa, factor VIIa, and fibrinogen, as well as inhibition of von Willebrand factor and tissue plasminogen activator in the patients with reduced renal function [8,9]. There is also a report of a rare case of ADPKD patient in which a thrombus formation was observed in the inferior vena cava (IVC) due to the compression of IVC by huge renal cysts [10].…”
Section: Discussionmentioning
confidence: 99%